Optimized deployment of anchors based on GDOP minimization for ultra-wideband positioning. Issue 3 (2nd September 2022) - Wang, Chuanyang; Ning, Yipeng; Wang, Jian; Zhang, Longping; Wan, Jun; He, Qimin
ABSTRACT: GDOP minimization criterion is applied to optimize positioning configuration. In this study, two kinds of GDOPs are introduced, the first kind of GDOP does not consider the clock error, the second kind considers. Cone configuration with lowest GDOP is discussed and extended for Ultra-wideband positioning. For three-dimensional scenarios, the configuration sets with lowest GDOP can be obtained based on the first kind of GDOP. Furthermore, the constraint statistics are considered to optimize global GDOP distribution in the positioning regions. We can believe that the cone configuration with constraints is effective to optimize the deployment of anchors.